2012
DOI: 10.1186/1471-2458-12-63
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Shiga toxin producing Escherichia coli in Australia, 2000-2010

Abstract: BackgroundShiga toxin-producing Escherichia coli (STEC) are an important cause of gastroenteritis in Australia and worldwide and can also result in serious sequelae such as haemolytic uraemic syndrome (HUS). In this paper we describe the epidemiology of STEC in Australia using the latest available data.MethodsNational and state notifications data, as well as data on serotypes, hospitalizations, mortality and outbreaks were examined.ResultsFor the 11 year period 2000 to 2010, the overall annual Australian rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
79
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 37 publications
5
79
1
1
Order By: Relevance
“…Although these SNP lineages are common to Australia, a larger set of isolates would need to be tested to confirm these host associations. Nonetheless, we believe that isolates belonging to SNP lineage IVb are likely to result in less frequent and severe disease outcomes (as determined by the frequency of HUS cases) in Australia based on E. coli O157 epidemiological data for this country (29). While compelling data exist to suggest that the pathogenic potential of E. coli O157 is related to the carriage of specific stx variants, additional underlying factors are also likely to influence lineage-associated virulence.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although these SNP lineages are common to Australia, a larger set of isolates would need to be tested to confirm these host associations. Nonetheless, we believe that isolates belonging to SNP lineage IVb are likely to result in less frequent and severe disease outcomes (as determined by the frequency of HUS cases) in Australia based on E. coli O157 epidemiological data for this country (29). While compelling data exist to suggest that the pathogenic potential of E. coli O157 is related to the carriage of specific stx variants, additional underlying factors are also likely to influence lineage-associated virulence.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the majority of U.S. cattle and human isolates were shown to belong to SNP lineage Ib, which is frequently associated with clinical disease in the United States (10). In comparison, Australia has a relatively low reported frequency of HUS cases (29) and the incidence of disease associated with E. coli O157 appears to be lower than the global average. Although the predominant SNP lineages identified in Australia have not previously been associated with human sources (10), a significant association of SNP lineage IVb with Australian humans was identified in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a growing number of human EHEC infections are caused by non-O157 EHEC strains (1)(2)(3)(4). Among non-O157 EHEC strains, O26:H11 has emerged as the most common serotype associated with severe diarrhea and HUS worldwide (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…In recent years, cumulative evidence from numerous countries has indicated that up to 30 to 60% of human EHEC infections are caused by non-O157 EHEC (5, 6; U.S. Department of Agriculture [USDA] risk profile for pathogenic non-O157 Shiga-toxin producing E. coli, http://www.fsis.usda.gov/wps/wcm/connect/92de0 38d-c30e-4037-85a6-065c3a709435/Non_O157_STEC_Risk_P rofile_May2012.pdf?MODϭAJPERES). Recent studies have shown that the number of non-O157 STEC infections sometimes surpasses the number of STEC O157 infections (7,8). Accordingly, the list of STEC associated with HUS has been extended to include serotypes O26:H11, O45:H2, O103:H2, O111:H8, O121: H19, O145:H28, and O157:H7 and their non-motile derivatives.…”
mentioning
confidence: 99%